Meta-Analysis: Heuristic Vee Learning Model and Mathematical Concept Understanding Ability - Suherni, Herni; Supriadi, Nanang; Dinda Pratiwi, Dona (Desimal: Jurnal Matematika, 2026)
Mathematical conceptual understanding is essential for enabling students to interpret mathematical ideas, connect concepts, and justify problem-solving procedures. However, many students still experience difficulty developing conceptual understanding because mathematics instruction often emphasizes procedural fluency rather than meaningful conceptual construction. The Heuristic Vee model has been proposed as an instructional approach that connects conceptual and methodological components of learning, yet empirical findings regarding its effectiveness remain fragmented across studies. This study conducted a group-contrast meta-analysis to examine the effect of the Heuristic Vee model on students’ mathematical conceptual understanding. Data were obtained from seven eligible empirical studies published between 2013 and 2023, selected through Publish or Perish from Google Scholar, Semantic Scholar, and Scopus. The included studies reported complete statistical information from experimental and control groups, including sample size, mean, and standard deviation. Effect sizes were calculated using standardized mean differences and analyzed with OpenMEE and JASP. The random-effects model produced a significant large pooled effect size of 2.529, indicating that Heuristic Vee-based instruction positively influenced students’ mathematical conceptual understanding. Subgroup analysis showed a significant large effect at the junior secondary level and in the Indonesian context, whereas higher education, Malaysia, and Turkey showed large numerical effects but limited statistical certainty due to small study representation. Heterogeneity was very high, and Egger’s test indicated possible funnel plot asymmetry, although fail-safe N and trim-and-fill analysis suggested relatively robust results. These findings indicate that Heuristic Vee is a promising instructional model for strengthening mathematical conceptual understanding when supported by appropriate scaffolding and contextual implementation.